Innovative Methods for Reducing Sodium in Cupcakes With Mechanical Leavening and Ozonized Water - Maxat N. Mamyrayev; Auyelbek Iztayev; Talgat K. Kulazhanov; Madina A. Yakiyayeva; Mira E. Yerzhanova; Erik B. Askarbekov; Bayan Zh. Muldabekova; Pernekul M. Maliktayeva; Sholpan A. Tursunbayeva (International Journal of Food Science)
This study developed a technology to prepare cupcakes with a reduced sodium content from fine whole-ground wheat flour and ozonated water. Cavitation technology was utilised to reduce the sodium content, to shorten the cooking time, and to improve the consistency of the dough by accelerated churning. The dough was obtained by cavitation loosening under compressed air pressure and increasing the speed to 900 rpm. The cupcake preparation was accelerated by increasing the number of revolutions, resulting in a more saturated dough and a two-to-threefold volume increase. This approach produced a product of good quality and eliminated baking powder from the recipe. The optimal parameters for preparing dough using accelerated ozone cavitation technology were determined: an ozone concentration of 3 mg/cm3, 900 rpm of the kneading body, and a dough chamber pressure of 0.3 MPa. This study has established that accelerated ozone cavitation technology contributes to ensuring food safety, increasing production efficiency, and ensuring the quality of the finished product. This technology allows manufacturers to obtain high-quality and safe flour confectionery products using an accelerated method.